IbM GERAKAN BANK SAMPAH SEKOLAH TINGKAT SEKOLAH DASAR DI KOTA MAKASSAR - Mappasere, Fatmawati Andi; Husein, Naidah (Forum Layanan IPTEKS Bagi Masyarakat (FLipMAS) Wilayah Bali, 2019)
Garbage became a serious problem particularly in the city. It was caused by indicipline human’s behaviour in managing their garbage. In order to change that behaviour, better garbage management that was started from elementary school level.Clean life behavior by managing garbage can be done by Bank Sampah Sekolah movement. This movement was social engineering to save environment through involving people at school to manage garbage by applying 5R principals (rethink, reduce, reuse, recycle and replant).Through this movement, it was expected that a paradigm changing on concept of garbage. If it was managed in better way, money can be generated. This community development program aimed to increase the capacity on managing Bank Sampah Sekolah for people in school. The research finding shown that better management on Bank Sampah Sekolah by following planning, organization, implementation, monitoring and evaluation was effective to increase clean life behavior and paradigm changing on garbage where it can be income generating.